2018
DOI: 10.1177/1945892418762644
|View full text |Cite
|
Sign up to set email alerts
|

Survivin and cortactin expression in sinonasal schneiderian (inverted) papilloma and associated carcinoma

Abstract: Nuclear survivin expression was significantly higher in SCCs than in IPs. Prospective, multi-institutional prognostic studies, preferably on an international scale (given the few cases treated at single institutions), are needed to confirm the role of survivin in IP malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A previous study found that nuclear survivin expression was significantly higher in sinonasal IP and IPwSCC tissue than in normal sinonasal mucosal tissue. 26 Interestingly, the expression of VEGF and survivin can be transcriptionally upregulated by FoxM1, which has also been reported in other tumor types. 27,28 Therefore, the increased expression of VEGF and survivin in sinonasal IP and IPwSCC may be associated with FoxM1.…”
Section: Discussionmentioning
confidence: 57%
“…A previous study found that nuclear survivin expression was significantly higher in sinonasal IP and IPwSCC tissue than in normal sinonasal mucosal tissue. 26 Interestingly, the expression of VEGF and survivin can be transcriptionally upregulated by FoxM1, which has also been reported in other tumor types. 27,28 Therefore, the increased expression of VEGF and survivin in sinonasal IP and IPwSCC may be associated with FoxM1.…”
Section: Discussionmentioning
confidence: 57%
“…Survivin, an inhibitor of apoptosis, is also found to be potentially correlated with SCC. Nuclear survivin expression was significantly higher in SCCs than in IPs in one study [60].…”
Section: Proteinsmentioning
confidence: 85%
“…Even the current WHO classification has not included "carcinoma ex sinonasal papilloma" among its topics, which might negatively affect the precise diagnosis of such a category [28]. It should also be noted that the IHC profile of this group is yet to be established, despite several IHC studies conducted in this context [27,[29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%